Production of human epidermal growth factor using adenoviral based system - Babak Negahdari; Zahra Shahosseini; Vahid Baniasadi (Wolters Kluwer Medknow Publications, 2016)
Epidermal growth factor (EGF), a growth factor involved in cell growth and differentiation, is a small polypeptide with molecular weight of approximately 6 kDa known to be present in a number of different mammalian species. Experimental studies in animals and humans have demonstrated that the topical application of EGF accelerates the rate of epidermal regeneration of partial-thickness wounds and second-degree burns. Due to its commercial applications, Human EGF (hEGF) has been cloned in several forms. In the present study, adenoviral based expression system was used to produce biologically active recombinant hEGF. The presence of secreted recombinant hEGF was confirmed by a dot blot and its expression level was determined by enzyme-linked immuno-sorbent assay . Moreover, biological activity of secreted hEGF was evaluated by a proliferation assay performed on A549 cells. For production of hEGF in a secretory form, a chimeric gene coding for the hEGF fused to the signal peptide was expressed using adenoviral based method. This method enables the production of hEGF at the site of interest and moreover it could be used for cell proliferation and differentiation assays in tissue engineering research experiments instead of using commercially available EGF.